2020
DOI: 10.1111/dth.14389
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidity and temperament‐character traits of the patients with lichen simplex chronicus: The relation with the symptom severity of the disease

Abstract: The aim of this study is to evaluate psychiatric comorbidity, temperament and character traits, depression and anxiety levels, and their relation with symptom severity in patients with lichen simplex chronicus (LSC). About 50 patients with LSC were enrolled in the study along with 49 controls. The Structured Clinical Interview for DSM-5 (SCID-5), Temperament and Character Inventory (TCI), Beck Anxiety Inventory (BAI), and Beck Depression Inventory (BDI) were administered to all subjects for psychiatric assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…This disorder is heavily documented with psychiatric comorbidities. The most common comorbidities include depressive disorders, especially major depression and dysthymic disorder; anxiety disorders, attention deficit/hyperactivity disorder, substance use disorder, psychotic disorders, dissociative disorders, obsessive compulsive disorders, conduct disorder, and impulse‐control disorders 16–18 . The psychiatric treatment revolves around treating the psychiatric comorbidities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This disorder is heavily documented with psychiatric comorbidities. The most common comorbidities include depressive disorders, especially major depression and dysthymic disorder; anxiety disorders, attention deficit/hyperactivity disorder, substance use disorder, psychotic disorders, dissociative disorders, obsessive compulsive disorders, conduct disorder, and impulse‐control disorders 16–18 . The psychiatric treatment revolves around treating the psychiatric comorbidities.…”
Section: Resultsmentioning
confidence: 99%
“…The most common comorbidities include depressive disorders, especially major depression and dysthymic disorder; anxiety disorders, attention deficit/hyperactivity disorder, substance use disorder, psychotic disorders, dissociative disorders, obsessive compulsive disorders, conduct disorder, and impulse‐control disorders. 16 , 17 , 18 The psychiatric treatment revolves around treating the psychiatric comorbidities. Psychotherapy, especially CBT, and supplemental therapies such as yoga, meditation, mindfulness, aerobic exercise, relaxation techniques, journaling, hypnosis, acupuncture, and biofeedback may be helpful.…”
Section: Resultsmentioning
confidence: 99%
“… 20 Yalçın et al found that 62% of 50 LSC patients had at least one psychiatric comorbidity, mostly major depressive disorder (32%), dysthymia (18%), and generalized anxiety disorder (12%). 21 Halvorsen et al stated that itch is a greater risk factor for psychological problems compared to chronic eczema without itch. 22 …”
Section: Discussionmentioning
confidence: 99%
“…LSC can occur secondary to other cutaneous conditions or present as a primary disorder, which is frequently associated with psychological stressors. 1,2 It most commonly occurs in females during middle to late adulthood and is seldom observed in pediatric populations. 3 A 15-year-old Caucasian female presented to our pediatric clinic for a well-child visit.…”
mentioning
confidence: 99%